Malaysia's defeat of armed communism : the second emergency, 1968 - 1989 - Ong, Weichong (New York : Routledge, 2015)
The Malayan Communist Party's (MCP) decisive defeat in 1960 led many academics and Counterinsurgency (COIN) experts to overlook the resurrection of its armed struggle in 1968. Most scholars continue to regard the so-called'Second Emergency' in Malaysia (1968-1989) as a non-event, and most of the recently published work on the MCP tends to focus on the earlier Malayan Emergency (1948-1960).
Includes bibliographical references (page 185-199) and index.
Keywords: Malayan Communist Party -- History; Communism -- Malaysia -- History; Insurgency -- Malaysia -- History; Counterinsurgency -- Malaysia -- History